Buprenorphine and HIV primary care: new opportunities for integrated treatment. - Khalsa, Jag; Vocci, Francis; Altice, Frederick; Fiellin, David; Miller, Veronica (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2006)
Drug abuse and infection with human immunodeficiency virus (HIV) are associated with high rates of morbidity and mortality, but, because of medical, social, and legal factors, opiate addiction/dependence is a major obstacle to successful treatment of disease--for example, treatment of acquired immunodeficiency syndrome (AIDS) with highly active antiretroviral therapy. In an effort to improve the opportunity for treatment of drug abuse and HIV infection, the Forum for Collaborative HIV Research, in collaboration with the Substance Abuse and Mental Health Services Administration, the National Institute on Drug Abuse, the Centers for Disease Control and Prevention, and other agencies, presented a workshop entitled "Buprenorphine in the Primary HIV Care Setting." Participants reviewed and discussed current issues, such as the introduction of and sources for the provision of buprenorphine in HIV primary care settings and strategies for integrating treatment of HIV-infected drug abusers, all of which are covered in this supplement.
Keywords: Antiretroviral Therapy, Highly Active; Buprenorphine; Delivery of Health Care, Integrated; Female; Follow-Up Studies; Health Services Research; HIV Infections; Humans; Incidence; Male; Narcotic Antagonists; Opioid-Related Disorders; Primary Health Care; Primary Prevention; Risk Assessment; Survival Analysis; Treatment Outcome; United States